Color Characteristics of Morning Glory (Ipomoea purpurea) Extract as a Natural Stain for Avian Blood Smear Preparations - Wahyuni, Sri; Hindun, Iin; Zaenab, Siti (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
Synthetic stains such as Giemsa and Wright remain the standard reagents for blood smear examination, but their repeated use in teaching laboratories raises concerns related to cost, handling safety, and chemical waste. This study evaluated the color characteristics of Morning Glory (Ipomoea purpurea) flower extract as a natural stain for avian blood smear preparations and identified the best-performing tested concentration under the present experimental conditions. A laboratory experiment was conducted using ethanol-macerated Morning Glory extract adjusted to pH 4 and tested at 70%, 80%, and 90%, with unstained smears, methylene blue, and Giemsa as comparators. Blood smears from Columba livia were observed microscopically and evaluated using an ordinal rubric covering clarity, contrast, structural integrity, intensity, and cleanliness, alongside UV-Vis absorbance measurement. The extract showed a maximum wavelength at 641 nm, and absorbance increased with concentration, reaching 2.836 AU at 90%. However, the best microscopic performance among the natural-stain treatments was obtained at 80%, which yielded the highest clarity and contrast scores within the extract group. Kruskal-Wallis analysis indicated significant differences among treatments for clarity (p = 0.003) and contrast (p = 0.001). Although the Morning Glory extract did not match the performance of methylene blue and Giemsa, the 80% preparation showed pilot-level potential as a greener alternative for teaching laboratories and initial smear observation. These findings should be interpreted cautiously because the study was limited to one avian source, relied primarily on visual scoring, and did not yet include objective image-based analysis or long-term stain-stability testing.